2006
DOI: 10.1080/01902140600959671
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation, Edema, and Peripheral Blood Changes in Lung-Compromised Rats After Instillation With Combustion-Derived and Manufactured Nanoparticles

Abstract: Increased exposure to pollution has been implicated in cardiovascular malfunction, and although studies show a relationship between PM10 and mortality, the exact biological causes are unclear. This study investigated how compromised lungs respond to instillation of nanoparticles, and the links between exposure to nanoparticles and the subsequent effects on the blood. Instillation of diesel exhaust particles and Cabosil caused significant permeability and inflammatory changes in both bleomycin-treated and contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 39 publications
2
19
0
Order By: Relevance
“…However, when 14-nm carbon black NPs were coadministered with a bacterial endotoxin, these particles intensively aggravated lipopolysaccharide (LPS) -induced pulmonary inflammation (17,27). Intratracheal instillation of Cabosil, a commercially available NP of amorphous SiO 2 , caused significantly increased inflammatory changes in rat lungs compromised by bleomycin (17). These data suggest that engineered NPs could potentiate the effects of other inhaled stimuli (27).…”
Section: Potential Adverse Pulmonary and Respiratory Effects Of Enginmentioning
confidence: 74%
See 2 more Smart Citations
“…However, when 14-nm carbon black NPs were coadministered with a bacterial endotoxin, these particles intensively aggravated lipopolysaccharide (LPS) -induced pulmonary inflammation (17,27). Intratracheal instillation of Cabosil, a commercially available NP of amorphous SiO 2 , caused significantly increased inflammatory changes in rat lungs compromised by bleomycin (17). These data suggest that engineered NPs could potentiate the effects of other inhaled stimuli (27).…”
Section: Potential Adverse Pulmonary and Respiratory Effects Of Enginmentioning
confidence: 74%
“…In addition to the proinflammatory effects, NPs may also exacerbate existing lung diseases (17,27). Inoue et al (27) have demonstrated that intratracheal administration of 14 nm and 56 nm carbon black NPs induced slight lung inflammation and significant pulmonary edema compared with the phosphate buffered saline (PBS)-treated mice.…”
Section: Potential Adverse Pulmonary and Respiratory Effects Of Enginmentioning
confidence: 99%
See 1 more Smart Citation
“…Instillation of ultrafine carbon black particles (~14 nm) intratracheally into rat lungs led to a marked increase in lactate dehydrogenase (LDH) levels in bronchoalveolar lavage (BAL) fluid (Li et al 1999). Intratracheal instillation of diesel exhaust particles (~30 nm) and an amorphous silicon dioxide (commercially available as Carbosil, ~7 nm) into lungs of male Sprague-Dawley rats increased air-blood barrier permeability, inflammation and edema formation, leading to a strong correlation of plasma viscosity with an index of type I cell injury (reflected as rat type I cell marker found in lung lavage fluid) (Evans et al 2006). By contrast, healthy mice did not appear to respond to ultrafine carbon and platinum particles (15 and 25 nm, respectively) when inhaled for up to 6 hours at 110 μg/mL (Oberdorster 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Intratracheal instillation of ultrafi ne DEPs into rat lungs increased both pulmonary infl ammation and air -blood barrier permeability (Miyabara et al, 1998 ;Tsurudome et al, 1999 ;Evans et al, 2006 ). Diesel exhaust UFPs also induced a neutrophilic infl ux in the lungs of mice and had DNA -damaging effects (Saber et al, 2005 ).…”
Section: Organic Compounds Diesel Exhaust Particles (Deps) and Cardmentioning
confidence: 99%